Brannigan's Land: A Month of Doomsdays - Book 3 - Johnstone, William W.; Johnstone, J. A. (Thorndike, Maine : Center Point Large Print, 2023)
"Something fishy is going on with the beef at Circle P. After a quick-and-dirty shootout with a small band of rustlers, Ty Brannigan and his son Matt do another count of their cattle -- and find they have fifty heads more than before. Seems the rustlers were hiding stolen cows from other ranches among the Brannigan herd. And thats just the tip of the cowpie. In jail, the rustlers rat out their partners to the local marshal. Theyre not just stealing cattle. Theyre plotting the biggest bank robbery in the countys bullet-riddled history. And this time, theyre going to make a real killing ... Months in the planning -- and just days away -- the countdown to doomsday has begun. Ty, Matt, and the town marshall must race against time to track down the robbers before they strike -- or innocent people will die. But the Brannigans arent afraid of danger. When the clock runs out -- and the shooting starts -- every mans days are numbered ..." -- Amazon.
Keywords: United States. -- Marshals Service -- Fiction; Outlaws -- Fiction; Bank robbers -- Fiction; Ranchers -- Fiction; West (U.S.) -- Fiction; Western fiction; Action and adventure fiction; Historical fiction; Downloadable electronic books; Electronic books